Impact of Strategic Intelligence on the sustainable competitive advantage of Industries Qatar (Global Journal of Management and Business Research, 2020)
The research aims to investigate the impact of strategic intelligence on the sustainable competitive advantage. The population of the study consists of managers of Industries Qatar, namely; Qatar Petrochemical Company, Qatar Fuel Additives Company, Qatar Fertiliser Company, and Qatar Steel. The researcher distributed the questionnaire to the whole population. One hundred and three questionnaires were returned and analyzed using SPSS and Amos statistical software packages. The results clarify that Strategic intelligence, as measured by foresight, future vision, strategic partnership, motivation, and systems thinking, had a significant impact on sustainable competitive advantages. Based on the study results; managers and decision-makers of Industries Qatar have to utilizing the components of strategic intelligence to study the internal and external organizational environment and how it is influenced by the external variables and how to hedge potential external threats.
Keywords: strategic intelligence; sustainable competitive advantage; industries qatar